Role of NFAT in the Progression of Diabetic Atherosclerosis - Cai, Yaoyao; Yao, Haipeng; Sun, Zhen; Wang, Ying; Zhao, Yunyun; Wang, Zhongqun; Li, Lihua (Frontiers in Cardiovascular Medicine, 2021)
Nuclear factor of activated T cells (NFAT) is a kind of transcription factor with a multidirectional regulatory function, that is widely expressed in immune cells, including cells in the cardiovascular system, and nonimmune cells. A large number of studies have confirmed that calcineurin/NFAT signal transduction is very important in the development of vascular system and cardiovascular system during embryonic development, and plays some role in the occurrence of vascular diseases such as atherosclerosis, vascular calcification, and hypertension. Recent in vitro and in vivo studies have shown that NFAT proteins and their activation in the nucleus and binding to DNA-related sites can easily induce the expression of downstream target genes that participate in the proliferation, migration, angiogenesis and vascular inflammation of vascular wall related cells in various pathophysiological states. NFAT expression is regulated by various signaling pathways, including CD137-CD137L, and OX40-OX40L pathways. As a functionally diverse transcription factor, NFAT interacts with a large number of signaling molecules to modulate intracellular and extracellular signaling pathways. These NFAT-centered signaling pathways play important regulatory roles in the progression of atherosclerosis, such as in vascular smooth muscle cell phenotypeice transition and migration, endothelial cell injury, macrophage-derived foam cell formation, and plaque calcification. NFAT and related signaling pathways provide new therapeutic targets for vascular diseases such as atherosclerosis. Hence, further studies of the mechanism of NFAT in the occurrence and evolution of atherosclerosis remain crucial.